Nitric Oxide and Salmonella Pathogenesis - Henard, Calvin A.; Vazquez-Torres, Andres (Frontiers in Microbiology, 2011)
Nitric oxide (NO) and its congeners contribute to the innate immune response to Salmonella. This enteric pathogen is exposed to reactive nitrogen species (RNS) in the environment and at different anatomical locations during its infectious cycle in vertebrate hosts. Chemical generation of RNS enhances the gastric barrier to enteropathogenic bacteria, while products of the Salmonella pathogenicity island 1 (SPI1) type III secretion system and Salmonella-associated molecular patterns stimulate transcription of inducible NO synthase (iNOS) by cells of the mononuclear phagocytic cell lineage. The resulting NO, or products that arise from its interactions with oxygen (O2) or iron and low-molecular weight thiols, are preferentially bacteriostatic against Salmonella, while reaction of NO and superoxide (O2-) generates the bactericidal compound peroxynitrite (ONOO-). The anti-Salmonella activity of RNS emanates from the modification of redox active thiols and metal prosthetic groups of key molecular targets of the electron transport chain, central metabolic enzymes, transcription factors, and DNA and DNA-associated proteins. In turn, Salmonella display a plethora of defenses that modulate the delivery of iNOS-containing vesicles to phagosomes, scavenge and detoxify RNS, and repair biomolecules damaged by these toxic species. Traditionally, RNS have been recognized as important mediators of host defense against Salmonella. However, exciting new findings indicate that Salmonella can exploit the RNS produced during the infection to foster virulence. More knowledge of the primary RNS produced in response to Salmonella infection, the bacterial processes affected by these toxic species, and the adaptive bacterial responses that protect Salmonella from nitrosative and oxidative stress associated with NO will increase our understanding of Salmonella pathogenesis. This information may, in turn, assist in the development of novel therapeutics against this common enteropathoge